Software development for deformation detection using geodetic methods - Md. Som, Zainal Abidin (UTM, 2005)
Geodetic deformation surveys have been used in many tasks such as the monitoring of engineering structures, land subsidence and other related applications. As results, the analysis of deformation has become a subject of intensive studies of many professional groups which besides surveyors and geodesist include geotechnical and structural engineers, as well as geophysists and geologists. One of the main tasks in deformation analysis is the handling of least squares adjustment of the two-epochs of geodetic observations data. Another important aspect in such analysis is on the question of selecting a proper control point as datum in the adjustment computation. The adjustment results were then further analyzed to obtain a clear picture of deformation. One way of depicting the deformation is by creating a graphical trend analysis. This report describes the effort of developing Fredy04, a software for analyzing the deformation using geodetic methods. The computational methodology adopted in the software is based on the methodology known as the Fredericton Approach. The working procedures of the software were then implemented to analyze the deformation of a simulation deformation network which consist of geodetic observations in the form angle and distance measurements.